Direct Laser Writing of Graphene Made from Chemical Vapor Deposition for Flexible, Integratable Micro‐Supercapacitors with Ultrahigh Power Output. Issue 27 (17th May 2018) - Ye, Jianglin; Tan, Huabing; Wu, Shuilin; Ni, Kun; Pan, Fei; Liu, Jie; Tao, Zhuchen; Qu, Yan; Ji, Hengxing; Simon, Patrice; Zhu, Yanwu
Abstract: High‐performance yet flexible micro‐supercapacitors (MSCs) hold great promise as miniaturized power sources for increasing demand of integrated electronic devices. Herein, this study demonstrates a scalable fabrication of multilayered graphene‐based MSCs (MG‐MSCs), by direct laser writing (DLW) of stacked graphene films made from industry‐scale chemical vapor deposition (CVD). Combining the dry transfer of multilayered CVD graphene films, DLW allows a highly efficient fabrication of large‐areal MSCs with exceptional flexibility, diverse planar geometry, and capability of customer‐designed integration. The MG‐MSCs exhibit simultaneously ultrahigh energy density of 23 mWh cm −3 and power density of 1860 W cm −3 in an ionogel electrolyte. Notably, such MG‐MSCs demonstrate an outstanding flexible alternating current line‐filtering performance in poly(vinyl alcohol) (PVA)/H2 SO4 hydrogel electrolyte, indicated by a phase angle of −76.2° at 120 Hz and a resistance–capacitance constant of 0.54 ms, due to the efficient ion transport coupled with the excellent electric conductance of the planar MG microelectrodes. MG–polyaniline (MG‐PANI) hybrid MSCs fabricated by DLW of MG‐PANI hybrid films show an optimized capacitance of 3.8 mF cm −2 in PVA/H2 SO4 hydrogel electrolyte; an integrated device comprising MG‐MSCs line filtering, MG‐PANI MSCs, and pressure/gas sensors is demonstrated. Abstract : Flexible multilayered graphene‐based micro‐supercapacitors (MG‐MSCs) with an ultrahigh power density in an ionogel electrolyte are obtained by direct laser writing (DLW) of graphene films made from mass chemical vapor deposition. Notably, such MG‐MSCs demonstrate an outstanding flexible alternating‐current line‐filtering performance in hydrogel electrolyte. DLW shows potential for scaling to large area and for integration with other devices.